Casa Moimenta: Transformação, simplificação, método - Francisco Tavares Ascensão (2015)
This is a journey through one project. A project for a house in Moimenta, Cabeceiras de Basto, transformation of a group of small buildings (now ruins) that used to be rural dwellings into a house for temporary accomodations on holidays. The investigation finds in the first volume a steady metric of loose fragments, composed in a logical sequence, a good strategy for the materialization of an approach to the complexity and uncertainty of a project action, that finds moments of high precision, by going through fogs and difuse landscapes, running away from the rigidity imposed by the layouts of its final elements. In the second volume, almost a construction book, the strict and objective representations of the study case such as the topographical and photographical survey are combined with the final drawings. This way, one navigates between these two realities, that complete each other in a more informed reading, an understanding that is not limited to the formal comprehension of the proposal.